ANALISIS TINGKAT BAHAYA EROSI DI SUB DAS BANYUHIRANG DAS MALUKA KOTA BANJARBARU - Rahmadi Rahmadi; Muhammad Ruslan; Syarifuddin Kadir (Jurnal Sylva Scienteae, 2020)
In understanding of  climate characteristics in Indonesia in which  rainfall is relatively high, and the sun shine is relatively  long, combined with the  activities of shifting farming and the traditional soil preparation  and forest fire in the dry season , the properties of soil and foret land in genral has become worsening. By the action  erodibility of  rain water and  the fragile properties of soil  will disturb  the hidro=orology  of  land which will raise  the level of erosion hazard  (LEH). The condition also causes  soil  degradation of soil  fertility and reduced  agriculture production. The objective of research is to analyse   the level of erosion hazard    (LEH) in the area of sub-watershed of Banyuhirang, watershed of Maluka, Banjarbaru municipality. The research method is  the arrangement of data-spatiAl of forest land in terms of land unit  combinrd with land cover of forest, plantation, shrub and so on.   The calculation leh  uses the formula  of universal soil loss equation  (USLE). The result of research is as follows.  For the forest cover of lu-13, lu-24 and lu-15  the leh is  I-R whis is  relatively small and  medium for  and IIS  for 81,96 ha.   For plantation land cover of lu-02 and lu-09, leh  is is  i-R  for 3.417 ha; for plantation land cover of lu-05 and lu-08, leh is  leh is II-S  for 1.004,,93. Ha.  For shrub land cover of lu-lu-01 and lu-04, the leh  is III-B for 5.166,17 ha. For shrub land cover of lu-07 and lu-11, the leh is  IV SB  for 437,73 ha.  And finally  for the bare land of lu- lu-03, lu-05, lu-07 and lu-10  and lu-12, the leh is  IV SB   for   1.739,72  ha.Keywords :  levelof erosion hazard; land cover